Age and Growth Properties of Acanthobrama marmid Heckel, 1843 Population Inhabiting Uzuncayir Damlake (Tunceli/Turkey) - Coban, Mehmet Zulfu; Yuksel, Fahrettin (Medwell Online, 2013)
This study was aimed to investigate the some growth properties of Acanthobrama marmid Heckel, 1843 population in Uzuncayir Dam Lake (Tunceli/Turkey) between May 2011 to September 2012. A total of 604 A. marmid samples (340 males and 264 females) were caught from Uzimcayir Darn Lake; the age composition of the specimens ranged between 1-9 years. The overall sex ratio (females/males) was 1:0.78. Total lengths of specimens ranged from 8.80-27.80 cm and weights ranged from 6.20-182.00 g. The von Bertalanffy growth parameters were L.-0= 28.25 cm, K = 0.26 year and to = -0.90 year for males andLc, = 28.49 cm, K = 0.23 year' and t(0) = -1.24 year for females. The length-weight relationship was found as W = 0.009 /T1,39 in males and W = 0.012x in females. The growth perforrnance index (0') values of males, females and all samples were 2.317, 2.271 and 2.301, respectively. The condition factor values varied between 0.61-1.30 for entire population.
Keywords: Uzuncayir Darn Lake; Acanthobrama mannid; age; growth parameter; condition factor